2013
DOI: 10.1001/jamaoto.2013.5303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Reward System on Resident Research Productivity

Abstract: After implementation of a point-based reward system, resident research activity increased. The data suggest that this system may encourage resident research, although further refinement may be required to promote higher-quality research endeavors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 19 publications
1
63
0
Order By: Relevance
“…As expected, the “other” rotation had the highest well‐being; these rotations were mainly off service, resulting in less stress due to a 16‐hour shift, 80‐hour work week,17 more flexible/shorter hours, and less stress from the continuous scrutiny to excel in front of their own future peers. Pediatric otolaryngology and head and neck oncology had higher sleepiness compared to the research rotation, likely due to longer operative times18 and greater clinical or teaching duties on these rotations 19. More sleepiness was also found in the Head and Neck rotation by Nida et al20 In our institution, the research rotation has dedicated research time without clinical duties unless emergencies arise, giving the resident more control over schedule and life.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…As expected, the “other” rotation had the highest well‐being; these rotations were mainly off service, resulting in less stress due to a 16‐hour shift, 80‐hour work week,17 more flexible/shorter hours, and less stress from the continuous scrutiny to excel in front of their own future peers. Pediatric otolaryngology and head and neck oncology had higher sleepiness compared to the research rotation, likely due to longer operative times18 and greater clinical or teaching duties on these rotations 19. More sleepiness was also found in the Head and Neck rotation by Nida et al20 In our institution, the research rotation has dedicated research time without clinical duties unless emergencies arise, giving the resident more control over schedule and life.…”
Section: Discussionsupporting
confidence: 50%
“…Pediatric otolaryngology and head and neck oncology had higher sleepiness compared to the research rotation, likely due to longer operative times 18 and greater clinical or teaching duties on these rotations. 19 More sleepiness was also found in the Head and Neck rotation by Nida et al 20 In our institution, the research rotation has dedicated research time without clinical duties unless emergencies arise, giving the resident more control over schedule and life.…”
Section: Discussionmentioning
confidence: 54%
“…Barhyte and Redman (1993) also reported that a research support system, including access to statistical consultation, would improve research productivity of nursing faculty. Studies of other, related disciplines have shown that other factors are necessary as well; for example, in medicine, Chang and Mills (2013) reported that not only intellectual input but also mentorship and appropriate encouragement were important to improve research productivity for young doctors. However, no study has focused on the research productivity of young nursing faculty.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, residents' work in the operating room represents financial loss for surgical specialties, which has been well documented in general surgery [30], ear-nose-throat surgery [31][32][33], ophthalmology [34,35], and endoscopy [36]. For example, in a recent study on surgical residents performing mastectomies, the Saint Barnabas Medical Center group found that the additional calculated time required by surgical residents to perform mastectomies was 41 366 min for 1063 mastectomy cases (with and without reconstruction) over a 6-year period, which corresponded to an increase in operating room costs by $620 340 [30].…”
Section: Cost Of Residency Education Program In Generalmentioning
confidence: 99%